Trypanosomatid-Caused Conditions: State of the Art of Therapeutics and Potential Applications of Lipid-Based Nanocarriers - Muraca, Giuliana; Berti, Ignacio Rivero; Sbaraglini, María L.; Fávaro, Wagner J.; Durán, Nelson; Castro, Guillermo R.; Talevi, Alan (Frontiers in Chemistry, 2020)
Despite new therapeutic alternatives have progressively been incorporated to the arsenal of approved drugs against trypanosomatid-caused neglected infectious diseases (i.e. African trypanosomiasis, Chagas disease and Leishmaniasis), many of the available therapeutics display substantial limitations, among them limited efficacy, safety issues / undesirable side effects, inconvenient routes of administration, drug resistance and inadequacy in insufficient health infrastructure settings. Nanovehicles combined with novel biocides could help circumventing at least some of such issues. Here, we review the current therapeutic options for trypanosomatid-caused diseases and the recent reports on nanolipid pharmaceutical carriers encapsulating approved drugs for African trypanosomiasis, Chagas disease and visceral and cutaneous leishmaniasis. Also, non-approved trypanocidal drugs delivered through lipid carriers are also explored. Finally, in the light of the reviewed reports, we discuss the perspectives in these fields, with a focus on the potential of last generation nanosystems (e.g. hybrid and targeted nanosystems).